Чебишовське наближення раціональним виразом функцій двох змінних - Малачівський, Петро Стефанович; Монцібович, Борис Романович; Пізюр, Ярополк Володимирович; Малачівський, Роман Петрович (Kamianets-Podilskyi National Ivan Ohiienko University, 2019)
The method for constructing of Chebyshev approximation by rational expression for function of two variables is proposed. Idea of the method is based on constructing the boundary power-average approximation in  norm with . Least square method with two weight functions is used to construct of this approximation. One weight function ensures the construction of power-average approximation, and another refines parameters of rational expression by linearization scheme. Iterative refinement of weight functions values is proposed. Results of test examples solving confirm the effectivity of proposed method